Who Bears the Welfare Costs of Monopoly? The Case of the Credit Card Industry - Kyle Herkenhoff; Gajendran Raveendranathan (Institute of Labor Economics (IZA), 2019)
How are the welfare costs from monopoly distributed across U.S. households? We answer this question for the U.S. credit card industry, which is highly concentrated, charges interest rates that are 3.4 to 8.8 percentage points above perfectly competitive pricing, and has repeatedly lost antitrust lawsuits. We depart from existing competitive models by integrating oligopolistic lenders into a heterogeneous agent, defaultable debt framework. Our model accounts for 20 to 50 percent of the spreads observed in the data. Welfare gains from competitive reforms in the 1970s are equivalent to a one-time transfer worth between 0.24 and 1.66 percent of GDP. Along the transition path, 93 percent of individuals are better off. Poor households benefit from increased consumption smoothing, while rich households benefit from higher general equilibrium interest rates on savings. Transitioning from 1970 to 2016 levels of competition yields welfare gains equivalent to a one-time transfer worth between 1.87 and 3.20 percent of GDP. Lastly, homogeneous interest rate caps in 2016 deliver limited welfare gains.
Keywords: D14; D43; D60; E21; E44; G21; 330; welfare costs of monopoly; consumer credit; competition; welfare